The system of „safe passage” in the female emigration movement of the victorian era - Kryuchkova, Natalia Dmitriyevna (Acta Scientiarum Socialium, 2012)
In the second half of the 19th century and at the beginning of the 20th, the British project of imperial consolidation attached a great importance to emigration, including female emigration, to white settler colonies of Great Britain. Emigrants ensured close connection between dominions and the mother country; they spread British values and British style of life. Therefore high morality of migrant women acquired a special significance. The process of crossing the ocean on the ship, which took some months, was the greatest danger for virtue and respectability of female emigrants. The efforts of British government and female emigration organizations to secure safe and respectable passage of female emigrants to the new homeland are investigated in this article.
Keywords: ship; assisted emigration; safety; control